Ekonomi Kreatif dan UMKM Risol: Strategi Membangun Identitas Produk di Tengah Kompetisi Kuliner - Harahap, Nasya Putri Afrida; Ramadani , Fairuza; Berutu, Cinta Zuluna; Hafis, Egas; Zainarti, Zainarti (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2025)
Spring roll MSMEs face increasingly fierce culinary competition, particularly amid product diversification, changing consumer preferences, and demands for continued differentiation. This study aims to analyze product identity development strategies that can strengthen the position of spring roll MSMEs in both local and digital markets. Using a qualitative approach with a document analysis design, data were collected through document and marketing searches, as well as content analysis of promotional materials to capture actual practices in building product image. The research findings indicate that flavor innovation plays a significant role as a differentiation tool, enabling spring roll products to appear unique through the exploration of ingredient variations, non-traditional flavor combinations, and adaptation to taste trends, thus creating memorable sensory value for consumers. Visual branding and packaging design have been shown to increase brand visibility through consistency in color, typography, and graphic elements that emphasize product character while strengthening quality associations. Storytelling makes a strong contribution to building unique value by linking products to narratives of origin, creative processes, and authentic messages that trigger consumer emotional engagement and expand product meaning. In addition, responsive distribution strategies, such as the use of digital platforms, delivery services, and adaptive point-of-sale arrangements, along with a holistically designed customer experience through friendly service, fast response, and quality assurance, encourage consistent strengthening of product identity. The theoretical implications of this research enrich the study of the creative economy by providing a comprehensive understanding of the construction of MSME product identity. In contrast, its practical implications offer strategic guidelines for business actors to increase competitiveness based on creativity and consumer experience.